Dispersion of buoyant emissions from low level sources in urban areas: water channel modelling. (1st January 2013) - Pournazeri, Sam; Schulte, Nico; Tan, Si; Princevac, Marko; Venkatram, Akula
A laboratory study was done to investigate dispersion of buoyant emissions from near surface sources in urban areas. Ground level concentrations under different surrounding building geometries were measured using a newly developed system based on laser induced fluorescence. In the presence of upstream buildings AERMOD (AMS/U.S. EPA regulatory dispersion model) is unable to explain concentrations close to the source. Plume visualisations and velocity measurements show that upstream buildings induce low velocity and a highly turbulent region near the stack, which increases the plume rise and induces rapid vertical mixing. Also, the urban canopy imposes a length scale on the horizontal turbulence, causing the plume to spread laterally with the square root of distance (~ x 1/2 ) rather than linearly as occurs in open terrain. A Gaussian-based dispersion model which accounts for these effects performs substantially better in predicting ground level concentrations associated with buoyant emissions from distributed power generators in urban areas.